Antidemocratic populism in power: comparing Erdoğan's Turkey with Modi's India and Netanyahu's Israel. Issue 8 (16th November 2020) - Rogenhofer, Julius Maximilian; Panievsky, Ayala
ABSTRACT: By the end of the second decade of the twenty-first century, populists have taken charge in Turkey, India and Israel, all previously heralded as exceptional democracies in difficult regions. This moment offers a unique opportunity to explore populism in power outside Europe and the Americas, in three states shaped by deep social, ethnic and religious divisions. This article locates Turkey, India and Israel within a global wave of electorally successful populist movements. It explores how populism can jeopardize democratic choice in deeply divided societies and whether Erdoğan's capture of democracy in Turkey offers a blueprint for the political strategies employed by Modi and Netanyahu. In unravelling parallels between the three administrations, our analysis uncovers a common populist playbook of neoliberal economic policies, the leveraging of ethnoreligious tensions as well as attempts to denigrate independent news media, by portraying it as the "enemy of the people". Although their position on the spectrum between democracy and authoritarianism differs, our analysis reveals striking continuities in the erosion of democracy in Turkey, India and Israel as a result of these policies, thus highlighting the vulnerability of political systems, particularly those of deeply divided societies, to democratic decay.